2019
DOI: 10.1051/0004-6361/201936963
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties and detectability of supermassive stars in protoglobular clusters at high redshift

Abstract: Context. Globular clusters (GCs) contain multiple stellar populations with peculiar chemical compositions. Pollution of the intracluster gas by an early population of fast-evolving stars is the most common scenario for explaining the observations. Stars with masses in excess of 1000 M have recently been suggested as potential polluters. Aims. We investigate the spectral properties of proto-GCs that would host a supermassive star (SMS). Our main goal is to quantify how such a star would affect the integrated li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 131 publications
(173 reference statements)
1
33
0
Order By: Relevance
“…Even though current Euclid and WFIRST detection limits (26 and 28, respectively) are well below the H band magnitudes of both stars at 𝑧 ∼ 6 − 20, both of them would be able to detect blue SMSs as even a slight amount of gravitational lensing will boost the fluxes of these blue SMSs above the detection limits of these two missions. Martins et al (2020) found some important spectral features in the observational properties of SMSs with mass range ∼ 10 3 − 5 × 10 4 M . They have computed the spectra of SMSs for non-local thermal equilibrium spherical stellar atmosphere models.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Even though current Euclid and WFIRST detection limits (26 and 28, respectively) are well below the H band magnitudes of both stars at 𝑧 ∼ 6 − 20, both of them would be able to detect blue SMSs as even a slight amount of gravitational lensing will boost the fluxes of these blue SMSs above the detection limits of these two missions. Martins et al (2020) found some important spectral features in the observational properties of SMSs with mass range ∼ 10 3 − 5 × 10 4 M . They have computed the spectra of SMSs for non-local thermal equilibrium spherical stellar atmosphere models.…”
Section: Introductionmentioning
confidence: 82%
“…Upcoming next generation telescopes e.g. James Webb Space Telescope (JWST), Euclid and WFIRST will be able to detect SMSs at 𝑧 ∼ 6 − 20 (Surace et al 2018(Surace et al , 2019Woods et al 2020;Martins et al 2020). The number of SMSs per unit redshift per unit solid angle, which are expected to be detected at a redshift 𝑧, is given by:…”
Section: Introductionmentioning
confidence: 99%
“…On the theoretical side, evolutionary synthesis models are developed to predict the characteristics of proto-GCs in the early Universe (Renzini 2017;Pozzetti et al 2019). In this context, Martins et al (2020) developed the first synthetic models of proto-GCs hosting multiple stellar populations and a SMS. They compute theoretical combined spectra and synthetic photometry in UV, optical, and near-IR bands over a wide range of redshift (1 to 10), and predict the detectability of cool SMS in proto-GCs through deep imaging with JWST NIR-CAM camera.…”
Section: The Rich Chemical Footprints Of Gcs and Viable Channels To Their Originmentioning
confidence: 99%
“…It may come as a surprise that SMS would be difficult to find observationally. Martins et al (2020) predicted the detectability of cool SMS in proto-GCs at high redshift through deep imaging with JWST NIRCAM camera. One problem at low redshift however is that clusters that would be massive enough are not found in the Milky Way.…”
Section: Supermassive Star Modelmentioning
confidence: 99%